2018
DOI: 10.1176/appi.neuropsych.16120322
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoid Receptor Genetic Variants and Response to Fluoxetine in Major Depressive Disorder

Abstract: Hyperactivity of the hypothalamic pituitary adrenocortical (HPA) axis is one of the main clinical findings in depression. The HPA axis is interrelated with glucocorticoid signaling via glucocorticoid receptors (GCRs). Thus, functional genetic variants on GCRs might influence therapeutic outcomes in depression. The aim of the present study was to investigate the association between three functional polymorphisms (rs41423247, rs6195, and rs6189/rs6190) on GCR and response to fluoxetine in a group of depressed pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 59 publications
1
11
0
Order By: Relevance
“…A report in Dutch population however showed a positive association of the mutant form of rs6189/rs6190 polymorphism with MDD and antidepressant treatment but lack of associa-tion with regard to rs6195 [38]. Confirming our results, a previous report in an Iranian depressed population is suggestive of lack of association between these variants and response to fluoxetine [30]. These conflicting results might be due to ethnical differences on one hand and the low frequencies of these two rare genetic variants in various populations.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…A report in Dutch population however showed a positive association of the mutant form of rs6189/rs6190 polymorphism with MDD and antidepressant treatment but lack of associa-tion with regard to rs6195 [38]. Confirming our results, a previous report in an Iranian depressed population is suggestive of lack of association between these variants and response to fluoxetine [30]. These conflicting results might be due to ethnical differences on one hand and the low frequencies of these two rare genetic variants in various populations.…”
Section: Discussionsupporting
confidence: 67%
“…DNAs of both control and case group were extracted using whole blood and by a standard protocol [29]. PCR amplification of rs41423247, rs6195 and rs6189/rs6190 was performedusing primers and enzymes listed in Table-2.The PCR amplification of variants was performed as previously described [30]. After 3-16 hours of incubation, for separating digested fragments electrophoresis on agarose (Invitrogen Ultra Pure®) gel 2% was performed After staining with ethidium bromide the gel was visualized in a UV trans illuminator.…”
Section: Dna Extraction and Genotypingmentioning
confidence: 99%
“…In addition, there are evidences for an antidepressant response via glucocorticoid receptors (GRs) where it has been demonstrated that sertraline increases human hippocampal neurogenesis via a GR-dependent mechanism [107]. A recent study has shown the significant association of rs41423247 polymorphism with fluoxetine response in depressed patients [10]. Another study of haplotype-tag SNPs (rs1876828, rs242939 and rs242941) in CRHR1 shown the significantly improved response to antidepressants among highly anxious patients homozygous for the GAG haplotype, suggesting the possible role of CRHR1 and other stress-inflammatory pathway genes in variable antidepressant response [108,109].…”
Section: Discussionmentioning
confidence: 99%
“…Different inflammation-related biomarkers were discussed as markers of TRD ( Strawbridge et al., 2019b ), mainly soluble factors, such as pro-inflammatory cytokines and C-reactive protein (CRP) ( Uher et al., 2014 ); ( Chamberlain et al., 2019 ), but also cellular immunophenotype ( Lynall et al., 2020 ), and markers of hypothalamic–pituitary–adrenal (HPA) axis activity ( Nouraei et al., 2018 ); ( O'Connell et al., 2018 ). Biomarkers have been broadly defined as indicators of biological or pathogenic processes or responses to an exposure or intervention ( Food and Drug Administration and National Institutes of Health, 2016 ), and are critical to translate basic scientific concepts into diagnostic and therapeutic developments, improving clinical care ( Robb et al., 2016 ).…”
Section: Biological Correlates Of Trd: the Role Of Inflammation And Gene Expression Signaturesmentioning
confidence: 99%